Environmental sustainability attitudes among older Arabs in Israel: Psychometric testing of the Arabic SustainABLE-16 and SustainABLE-8 - AboJabel, Hanan; Ayalon, Liat; van Hoof, Joost; Dikken, Jeroen (Acta psychologica, 2025)
Climate change has increased the need for sustainable lifestyles, including among older adults. Environmental attitudes shape these practices, yet little is known about such attitudes among older adults, especially in minority groups such as older Arabs in Israel. Without culturally adapted tools, assessing attitudes or designing effective policies is challenging. The SustainABLE-16 and SustainABLE-8 questionnaires were designed to measure environmental attitudes but have not been translated or validated in Arabic. This study aimed (1) to translate, culturally adapt, and evaluate the validity and reliability of the Arabic versions of the SustainABLE-16 and SustainABLE-8 among older Arabs in Israel; and (2) to assess participants' environmental sustainability attitudes. A convenience sample of 202 Arab adults aged 60+ (mean age = 74.3; 65.3 % women) participated. Confirmatory Factor Analysis (CFA) of the Arabic SustainABLE-16 supported the original three-factor structure (environmental beliefs, pro-environmental behaviors, financial position), with acceptable loadings (all > 0.40) except item 16 (0.288), which was removed. The revised 15-item version showed good model fit (χ2/df = 2.178, CFI = 0.958, TLI = 0.944, SRMR = 0.074, RMSEA = 0.077) and strong internal consistency (Composite Reliability [CR] = 0.78–0.87). The SustainABLE-8 showed excellent fit (χ2/df = 0.859, CFI = 1.000, TLI = 1.003, SRMR = 0.031, RMSEA = 0.000), with all items loading >0.40 and CR values of 0.54–0.80. Evidence for face, content, convergent, discriminant, and cross-group validity was established. Overall, participants reported low scores across domains, particularly in pro-environmental behaviors. The SustainABLE-15 and SustainABLE-8 are valid, reliable, and culturally appropriate tools for assessing sustainability attitudes in this population. Results emphasize the need for culturally tailored interventions promoting environmental awareness and behavior, while addressing economic barriers.